Integration as a Multi-way Process - Barbara Samaluk (AS: Andragoška Spoznanja)
This article explores innovative EU-funded migrant integration projects which emerged in Slovenia after the 2008 global economic crisis. It stems from sociological literature that conceptualises integration as a general societal phenomenon that shields against precarity. By conducting qualitative interviews with those running the studied projects and other stakeholders, this article explores the projects’ drivers, tactics, and their impact on established institutions. The findings show that the projects were established by proactive activists who utilised EU funds to professionalise their activities and engage in partnerships to develop needs-based, cross-sectional and networked provision that empowers migrants and benchmarks professional norms and standards for migrant integration. Its specific contribution lies in uncovering a multi-way integration process that moves away from mainstream approaches to integration, which segregate and demand change only from migrants, and also includes public institutions and servants, professionals and host societies as a whole.